Dominance-Driven Autocratic Political Orientations Predict Political Violence in Western, Educated, Industrialized, Rich, and Democratic (WEIRD) and Non-WEIRD Samples. (December 2020) - Bartusevičius, Henrikas; van Leeuwen, Florian; Petersen, Michael Bang
Given the costs of political violence, scholars have long sought to identify its causes. We examined individual differences related to participation in political violence, emphasizing the central role of political orientations. We hypothesized that individuals with dominance-driven autocratic political orientations are prone to political violence. Multilevel analysis of survey data from 34 African countries ( N = 51, 587) indicated that autocracy-oriented individuals, compared with democracy-oriented individuals, are considerably more likely to participate in political violence. As a predictor of violence (indexed with attitudinal, intentional, and behavioral measures), autocratic orientation outperformed other variables highlighted in existing research, including socioeconomic status and group-based injustice. Additional analyses of original data from South Africa ( N = 2, 170), Denmark ( N = 1, 012), and the United States ( N = 1, 539) indicated that the link between autocratic orientations and political violence reflects individual differences in the use of dominance to achieve status and that the findings generalize to societies extensively socialized to democratic values.